ANALISIS PROFITABILITAS USAHA OLAHAN COKELAT PADA INDUSTRI RUMAH TANGGA âSAâADAH AGENCYâ DI KOTA PALU - Erniwati, Ni Nengah (AGROTEKBIS, 2016)
The objective of this research was to find the financial capital structure and the maximum income earned by the âSaâadah Agencyâ and its profitability of chocolate products such aschocolate bar and rainbow chocolate in Palu. This research was conducted from May to June 2015. Respondents were five people included the home industry owner and its workers. The result of this research showed that the structure of the home industry financial capital had fixed assets which value was IDR 57,923,000.Â The maximum income of IDR 9,906,118 was generated during May to June 2015 with the average profitability of 2.78% indicating that for every IDR 1 increase in sale will generate profit of 2.78%.